2002
DOI: 10.1016/s0378-1097(02)00651-1
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and kinetics of lactate fermentation to acetate and propionate via methylmalonyl-CoA or acrylyl-CoA

Abstract: Fermentation balances and growth yields were determined with various bacteria fermenting lactate to acetate plus propionate either via methylmalonyl-CoA or via acrylyl-CoA. All strains fermented lactate to acetate plus propionate at approximately a 1:2 ratio. Growth yields of Propionibacterium freudenreichii were more than twice as high as those of Clostridium homopropionicum or Veillonella parvula. Hydrogen was formed as a side product to a significant extent only by V. parvula and Pelobacter propionicus; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 15 publications
(16 reference statements)
2
53
0
2
Order By: Relevance
“…The biomass increase was matched by increasing σ″ signals in both SIP columns (G1 and G2). Cell counts for the column sacrificially sampled immediately before phase II are omitted, because propionate was detected, suggesting that the bacteria fermented lactate (Seeliger, Janssen and Schink, ), and that the column did not behave as a replicate. Temporal trends in peak‐ σ″ from a non‐growth control column, inoculated with S. oneidensis , but devoid of NO 3 − and lactate, are compared with the SIP measurements in column G2 in Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The biomass increase was matched by increasing σ″ signals in both SIP columns (G1 and G2). Cell counts for the column sacrificially sampled immediately before phase II are omitted, because propionate was detected, suggesting that the bacteria fermented lactate (Seeliger, Janssen and Schink, ), and that the column did not behave as a replicate. Temporal trends in peak‐ σ″ from a non‐growth control column, inoculated with S. oneidensis , but devoid of NO 3 − and lactate, are compared with the SIP measurements in column G2 in Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A possible function of acryloyl‐CoA as terminal acceptor in an electron transport phosphorylation similar to fumarate reductase [32] appears unlikely as it has been shown that acryloyl‐CoA reductase is a soluble enzyme, which uses NADH rather than menaquinol as electron donor. Growth experiments with two lactate fermenting organisms confirm the conservation of only one ATP/acetate via the acryloyl‐CoA pathway [33]. Clostridium homopropionicum ferments lactate via acryloyl‐CoA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The latter pathway comprises additional electron transport phosphorylation via the oxidation of reduced ferredoxin and NADH by fumarate via menaquinol [32]. Hence, the low ATP yield in the β‐alanine fermentation by C. propionicum should increase the catabolic substrate flux, which in the presence of high β‐alanine concentrations enhances the growth rate [33] and probably keeps the concentration of the toxic acryloyl‐CoA at a low level.…”
Section: Discussionmentioning
confidence: 99%
“…In periods with low lactic acid concentrations, most likely lactic acid was produced but instantly consumed by secondary processes. Lactic acid can be converted to acetic and propionic acid by microbes using the acrylyl‐CoA or the methylmalonyl‐CoA pathway or solely to acetic acid by heterotrophic homoacetogens exploiting lactate dehydrogenase, pyruvate decarboxylase and the Wood‐Ljungdahl pathway . Alternatively, the reduction to 1,2‐propanediol and ethanol is possible .…”
Section: Discussionmentioning
confidence: 99%